Olive-Leaf Extracts Modulate Inflammation and Oxidative Stress Associated with Human H. pylori Infection - Jose Manuel Silvan; Esperanza Guerrero-Hurtado; Alba Gutiérrez-Docio; Teresa Alarcón-Cavero; Marin Prodanov; Adolfo J. Martinez-Rodriguez (MDPI AG, 2021)
Helicobacter pylori (H. pylori) is one of the major human pathogens and the main cause of pathological damages that can progress from chronic gastritis to gastric cancer. During the colonization of gastric mucosa, this bacterium provokes a strong inflammatory response and subsequent oxidative process, which are associated with tissue damage. Therefore, the objective of this research was to evaluate the ability of two olive-leaf extracts (E1 and E2) to modulate the inflammatory response and oxidative stress in H. pylori-infected human gastric AGS cells. The obtained results showed that both extracts significantly decreased interleukin-8 (IL-8) secretion and reactive oxygen species (ROS) production in human gastric AGS cells. Both extracts also showed antibacterial activity against different H. pylori strains. HPLC-PAD-MS characterization demonstrated that extract E1 was mainly composed of highly hydrophilic compounds, such as hydroxytyrosol (HT) and its glucosides, and it was the most effective extract as an antibacterial agent. In contrast, extract E2 was composed mostly of moderately hydrophilic compounds, such as oleuropein (OLE), and it was more effective than extract E1 as an anti-inflammatory agent. Both extracts exhibited similar potential to decrease ROS production. These results show the importance of standardizing the extract composition according to the bioactive properties that should be potentiated.